A Novel Mechanism of 17-AAG Therapeutic Efficacy on HSP90 Inhibition in MYCN-Amplified Neuroblastoma Cells - Hanna, Reine; Abdallah, Jad; Abou-Antoun, Tamara (Frontiers in Oncology, 2021)
Background: Neuroblastoma is the most common pediatric extra-cranial nervous system tumor, originating from neural crest elements and giving rise to tumors in the adrenal medulla and sympathetic chain ganglia. Amplification of MYCN confers increased malignancy and poorer prognosis in high-risk neuroblastoma. Our SILAC proteomics analysis revealed over-expression of HSP90 in MYCN-amplified IMR-32 compared to the non-MYCN amplified SK-N-SH human neuroblastoma cells, rendering them highly resistant to therapeutic intervention. Methods: We used cellular bio-functional (proliferation, migration/invasion, apoptosis, viability and stem-cell self-renewal) assays and Western blot analysis to elucidate the therapeutic efficacy of HSP90 inhibition with 17-AAG. Results: 17-AAG treatment significantly inhibited cellular proliferation, viability and migration/invasion and increased apoptosis in both cell lines. Moreover, drug treatment significantly abrogated stem-cell self-renewal potential in the MYCN-amplified IMR-32 cells. Differential tumorigenic protein expression revealed a novel mechanism of therapeutic efficacy after 17-AAG treatment with a significant downregulation of HMGA1, FABP5, Oct4, MYCN, prohibitin and p-L1CAM in SK-N-SH cells. However, we observed a significant up-regulation of p-L1CAM, MYCN and prohibitin, and significant down-regulation of Oct4, FABP5, HMGA1, p-ERK, cleaved/total caspase-3 and PARP1 in IMR-32 cells. Conclusions: HSP90 inhibition revealed a novel therapeutic mechanism of antitumor activity in MYCN-amplified neuroblastoma cells that may enhance therapeutic sensitivity.